Reactivity to addictive drugs in the methylazoxymethanol (MAM) model of schizophrenia in male and female rats. (17th February 2017) - Ruda-Kucerova, Jana; Babinska, Zuzana; Amchova, Petra; Stark, Tibor; Drago, Filippo; Sulcova, Alexandra; Micale, Vincenzo
Abstract: Objectives: Patients with schizophrenia often suffer comorbid substance abuse regardless of gender. However, the vast majority of studies are only conducted in male subjects. Therefore, the aim of these experiments is to assess addictive behaviors of both sexes in a neurodevelopmental model of schizophrenia induced by prenatal methylazoxymethanol (MAM) acetate exposure. Methods: MAM (22 mg/kg) was administered intraperitoneally on gestational day 17. Two studies were performed in the offspring: (1) an alcohol-drinking procedure to assess daily intake of 20% alcohol and relapse-like behavior after a period of forced abstinence; (2) Methamphetamine (METH) intravenous self administration (IVSA) followed by forced abstinence and reinstatement phases. Results: MAM exposure during the prenatal period did not change alcohol drinking regardless of sex. However, MAM females showed higher alcohol consumption in comparison to MAM males. The METH IVSA study revealed only a modest increase of drug consumption in MAM males, while there was no difference between the female groups. Reinstatement data showed no effect of the MAM model in either sex, but suggested increased responding in female rats. Conclusions: This study suggests that female sex and schizophrenia-like phenotype may work synergistically to enhance alcohol consumption. However, future research is needed to establish paradigms in which these findings would be readily assessed to test anti-addiction treatments.